6-(Hex-5-enyloxy)naphthalene-2-carboxylic acid - Lutfor, M. R.; M. M., Yusoff (International Union of Crystallography, 2014)
The asymmetric unit of the title compound, C17H18O3, comprises three independent molecules with similar geometries. In each molecule, the carbonyl group is twisted away from the napthalene ring system, making dihedral angles of 1.0 (2), 1.05 (19) and 1.5 (2). The butene group in all three molecules are disordered over two sets of sites, with a refined occupancy ratio of 0.664 (6):0.336 (6). In the crystal, molecules are oriented with respect to their carbonyl groups, forming head-to-head dimers via O—H O hydrogen bonds. Adjacent dimers are further interconnected by C—H O hydrogen bonds into chains along the a-axis direction. The crystal structure is further stabilized by weak C—H interactions.